War, law and humanity the campaign to control warfare, 1853-1914 - Crossland, James (Bloomsbury Academic, 2018)
War, Law and Humanity tells the story of the transatlantic campaign to either mitigate the destructive forces of the battlefield, or prevent wars from being waged altogether, in the decades prior to the disastrous summer of 1914. Starting with the Crimean War of the 1850s, James Crossland traces this campaign to control warfare from the scandalous barracks of Scutari to the shambolic hospitals of the American Civil War, from the bloody sieges of Paris and Erzurum to the combative conference halls of Geneva and The Hague, uncovering the intertwined histories of a generation of humanitarians, surgeons, pacifists and utopians who were shocked into action by the barbarism and depravities of war. By examining the fascinating personal accounts of these figures, Crossland illuminates the complex motivations and influential actions of those committed to the campaign to control war, demonstrating how their labours built the foundation for the ideas - enshrined in our own times as international norms - that soldiers need caring for, weapons need restricting and wars need rules